Dampak Industri Tahu Rumahan Terhadap Ekonomi, Sosial, dan Lingkungan: Studi Kasus di Desa Bakung Kecamatan Udanawu Kabupaten Blitar - Febrianti, Sakina Duwita; Fatmawati, Eli; Yuliasari, Septi; Imam Hanafi, Khoirul; Nur Pratiwi, Hany (ECOTAS, 2023)
The tofu home industry operation can discharge environmentally harmful wastewater. The question of this study is to know what are the economic, social and environmental impacts of the tofu home industry. The purpose of this study is to determine the impact of a tofu home industry on the economy, society and the environment. The research is qualitative research using a descriptive method. The information was obtained through observations and interviews with home-based tofu business owners, residents, and various workers. The results showed that the company help the surrounding community to meet their needs by the availability of works. In addition, awareness of the importance of healthy and rich protein foods such as tofu has changed the way of life of local. However, the tofu home industry has a disturbing impact on society and the river water ecosystem, where sometimes it still dumps waste water into the river, which can cause a fishy smell and make the river turn white.